2009
DOI: 10.1111/j.1095-8339.2008.00947.x
|View full text |Cite
|
Sign up to set email alerts
|

A molecular study of hybridization and homoploid hybrid speciation inArgyranthemum(Asteraceae) on Tenerife, the Canary Islands

Abstract: Examples of recurrent homoploid hybrid speciation are few. One often-cited example is Argyranthemum sundingii. This example includes two described species, A. lemsii and A. sundingii, resulting from reciprocal hybridization between A. broussonetii and A. frutescens on Tenerife. The four species and artificial F1 and F2 hybrids have previously been investigated morphologically and cytologically. Here, we examine population differentiation based on amplified fragment length polymorphism to get a better understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 40 publications
2
51
0
Order By: Relevance
“…Further, the variation between the different populations of a species and between different species is approximately equal (6.9% and 7.6%, respectively) and small, despite great morphological differences (as also found by Nesbitt et al [1995] for Eucalyptus globulus). This may suggest that the morphology is driven by selective forces, while the molecular markers studied are relatively selectively neutral and thus driven by other forces (Karhu et al 1996;Fjellheim et al 2009). The genetic diversity was expected to be higher within hybrid populations because they should contain alleles from both parental species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the variation between the different populations of a species and between different species is approximately equal (6.9% and 7.6%, respectively) and small, despite great morphological differences (as also found by Nesbitt et al [1995] for Eucalyptus globulus). This may suggest that the morphology is driven by selective forces, while the molecular markers studied are relatively selectively neutral and thus driven by other forces (Karhu et al 1996;Fjellheim et al 2009). The genetic diversity was expected to be higher within hybrid populations because they should contain alleles from both parental species.…”
Section: Discussionmentioning
confidence: 99%
“…This was, however, not the case for either the artificial hybrids or the intermediates. The explanation for the artificial hybrids may be the small sample size (10), while the intermediates might have lost diversity over generations as a result of genetic drift, inbreeding, and backcrossing (Scotti et al 2002;Chung et al 2005;Fjellheim et al 2009). Jørgensen and Mauricio (2005) found that their hybrid populations were genetically very similar to one of the parental populations and judged this to be caused by backcrossing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction of non-native species, habitat destruction through deforestation and development of human infrastructure are all well known to have a major impact on native island biodiversity (Whittaker and Fernández-Palacios 2007). Because of their often recent evolutionary origin, island endemics tend to hybridize easily despite morphological and ecological differences (Baldwin et al 1998;Francisco-Ortega et al 2000;Fjellheim et al 2009). Postzygotic barriers are typically weak (Carlquist and Cole 1974;Levin et al 1996), and hybrids are often fertile so that introgression can readily occur.…”
Section: Introductionmentioning
confidence: 99%
“…Homoploid hybrid speciation is seemingly more likely to occur between species that are less genetically divergent than those giving rise to allopolyploids (Chapman & Burke 1997). It was documented in the family Asteraceae only for the genera Argyranthemum (Gross & Rieseberg 2005;Fjellheim et al 2009), Artemisia (Garcia et al 2008), Centaurea (Pisanu et al 2011), Helianthus (Lai et al 2005;Buerkle & Rieseberg, 2007), Polymnia (Estes & Beck 2011),…”
Section: Introductionmentioning
confidence: 99%